2010
DOI: 10.2109/jcersj2.118.1154
|View full text |Cite
|
Sign up to set email alerts
|

Lithium intercalation properties of tetratitanates and octatitanates

Abstract: The lithium intercalation properties of alkai tetratitanate (Li 2 Ti 4 O 9 ·1.1H 2 O, Na 1.5 H 0.5 Ti 4 O 9 ·0.53H 2 O) and octatitanate with various amounts of hydrated water (H 2 Ti 8 O 17 ·nH 2 O; n = 0.41, 0.96, 1.5) were examined. Alkali tetratitanates were obtained by ion exchange of the starting tetratitanate hydrate (H 2 Ti 4 O 9 ·1.9H 2 O) and subsequent heat treatment. Octatitanates were prepared by heat treatment of the starting tetratitanate hydrate. The prepared titanates exhibited a reversible ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…43 A detailed discussion of the formation mechanism of H 2 Ti 8 O 17 has been reported in previous papers. 26,42 After increasing the annealing temperature to 400 °C, a well-crystallized structure with lattice fringes of about 0.36 nm and 0.62 nm can be clearly seen in Figure 4c, which corresponds to the (110) and (001) interplanar spacings of TiO 2 −B, respectively, and is consistent with previously reported values for bulk TiO 2 −B phase. 44 In addition, after the annealing temperature is increased to 550 °C, the interplanar spacings of 0.35 nm, 0.36 nm, and 0.62 nm shown in Figure 4d are in excellent agreement with the dspacing of the (101) plane of anatase TiO 2 and the (110) and (200) planes of TiO 2 −B, respectively.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…43 A detailed discussion of the formation mechanism of H 2 Ti 8 O 17 has been reported in previous papers. 26,42 After increasing the annealing temperature to 400 °C, a well-crystallized structure with lattice fringes of about 0.36 nm and 0.62 nm can be clearly seen in Figure 4c, which corresponds to the (110) and (001) interplanar spacings of TiO 2 −B, respectively, and is consistent with previously reported values for bulk TiO 2 −B phase. 44 In addition, after the annealing temperature is increased to 550 °C, the interplanar spacings of 0.35 nm, 0.36 nm, and 0.62 nm shown in Figure 4d are in excellent agreement with the dspacing of the (101) plane of anatase TiO 2 and the (110) and (200) planes of TiO 2 −B, respectively.…”
Section: Resultssupporting
confidence: 89%
“…On other hand, Idemoto et al recently reported the use of H 2 Ti 12 O 25 as novel anode materials for LIBs and depicted a higher capacity of 225 mA h g –1 compared to Li 4 Ti 5 O 12 (175 mA h g –1 ) with excellent cycling performance . This successfully illustrated the promise of using hydrogen titanium oxides (HTO) as a new class of anode materials for LIB applications. ,, …”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The reversible capacity was 180 ± 10 mAh g −1 , and this value is consistent with that of anatase-type TiO 2 or octatitanate synthesized by heating a tetratitanate at moderate temperature. 18,19 The increase in the reduction/oxidation peak current seems proportional to the sweep rate. Figure 2b shows cyclic voltammograms of S50 measured at a sweep rate of >1 mV s −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Based on the present results on the successful ion exchange reaction at room temperature, the production of functional hybrids from various layered alkali titanates by the solid-state reaction at room temperature is worth investigating further because of the following advantageous aspects, i.e., lower energy consumption, shorter reaction time, and no need to waste solvent compared to the conventional ion exchange reactions, which have been reported using the reactions in aqueous solutions as well as in molten salts. The ion exchange reactions of zeolites, , zirconium phosphate, and layered titanates (Tl 2 Ti 4 O 9 , K 2 Ti 6 O 13 , and Cs 0.7 [Ti 1.65 Mg 0.35 ]­O 4 ) without using solvents have been reported previously, where the reactions were done at higher temperature (above the melting point of the salts) for longer time (over 60 min) compared with the present reaction at room temperature within a few tens of minutes.…”
Section: Resultsmentioning
confidence: 95%